(untitled) (Journal of Asian Development Studies, 2025)
This paper evaluated the LULC dynamics of District Rahim Yar Khan, Pakistan, within 22 years (2000 2022) by applying geospatial methods such as remote sensing (RS) and Geographic Information System (GIS). The years 2000, 2008, 2013, 2018 and 2022 were selected as the years when satellite data were obtained, and the same years were selected for demographic, industrial and urban data collected from national census reports. After analysing the images, the parameters used to measure vegetation, built-up areas, and water bodies were NDVI (Normalised Difference Vegetation Index), NDBI (Normalised Difference Built-up Index), and NDWI (Normalised Difference Water Index). The land was classified under five categories, namely built-up, vegetation, fallow land, water bodies and barren land, which were supervised. The findings show that built-up areas have increased by 42 km2 in 2000 and 113 km2 in 2022. There were changes in vegetation cover, which reached its highest in 2008 (6485 km2) and lowest in 2018 (5440 km2), with the most significant increase in 2013. Changes in water bodies were also observed, with the lowest value of 159 km2 in 2008 and the highest of 187 km2 in 2018. Barren land reduced to 5468 km2, compared to 6719 km2 in 2012 and 2022, respectively, and fallow land increased to 1415 km2 in 2022, compared to 95 km2 in 2008. These results contribute to understanding the impacts of population increase, urbanisation, and agricultural development on land resources and provide key information for sustainable urban planning, land resource management, and the prediction of future changes in LULC in the area.